Addition of human milk fortifier in breast milk on increasing body weight of premature infants - Handayani, Binti Dwi; Mayasari, Ayu Citra; Kapti, Rinik Eko; Agelan, Jose Luis Llopis; Saidah, Qori Ila (Pediomaternal Nursing Journal, 2025)
Introduction: Human Milk Fortifier (HMF) is an additional supplement for breast milk that can meet the nutritional needs of premature. One of the efforts to support the growth of premature babies is to fulfill their nutritional intake. Objective: This study aims to determine the effectiveness of giving HMF to breast milk on increasing the weight of premature babies in Neonatal Intensive Care Unit. Methods: The research design used a quasi-experiment design with a pre-test and post-test nonequivalent control group design. The samples are premature babies treated in the NICU in Surabaya. The sample technique used purposive sampling of 25 respondents as the treatment group (breast milk + HMF) and 20 respondents as the control group (breast milk only). The instrument uses a questionnaire and observation sheet. Data were analyzed using the repeated measures ANOVA test and the independent sample t-test. The repeated measures ANOVA test results indicate a statistically significant difference in weight gain over time (P-value <0.05), demonstrating that HMF supplementation contributes more effectively to weight gain compared to breast milk alone. Results: The study demonstrated a significant increase in body weight over time in both the treatment group and the control group, as measured by the Fenton chart (weight on days 7, 14, 21, and 28) with a P-value = 0.000. Notably, the treatment group (HMF+breast milk) exhibited a more pronounced weight gain by day 28 compared with control group (breast milk only), with a P-value = 0.015, indicating the superior efficacy of breast milk+HMF in promoting weight gain. Conclusion: Adding human milk fortifier to breast milk effectively increases weight in premature infants due to its high calorie content. It is particularly beneficial for infants requiring fluid restrictions. Keywords: fenton chart, human milk fortifier, premature baby's weight, quasi-experiment non-equivalent control group design